Assessment of the Viticulture State, Challenges and its Development Potential in The Armavir Region Using Sample Surveys - Asatryan, Hovhannes («Տիր» հրատ.)
Viticulture (aka grapes production) is one of the most prominent branches of agriculture in the Armavir region of RA. In the past 30 years of independence, this sector experienced ups and downs and has a development trend that cannot be described as linear and growing. This research is devoted to assessing the current state of viticulture in the Armavir region of RA. The main purpose of the research is to reveal the existing obstacles that hinder further sector development. In the scope of that purpose, the possibilities and preconditions of further development of viticulture in the Armavir region were evaluated. Խաղողագործությունը ՀՀ Արմավիրի մարզի գյուղատնտեսության կարևորագույն ճյուղերից մեկն է։ Անկախության նախկին 30 տարիների ընթացքում այս ճյուղը ունեցել է վերելքներ և անկումներ, իսկ հիմա բնութագրվում է զարգացման այնպիսի տրենդով, որը աճող չի կարելի համարել։ Այս հոդվածը ուղղված է ՀՀ Արմավիրի մարզում խաղողագործության ներկայիս վիճակի գնահատմանը։ Հետազոտության հիմնական նպատակն է` բացահայտել այն առկա խոչընդոտները, որոնք խաթարում են խաղողագործության հետագա զարգացումը։ Այդ նպատակի իրականացման շրջանակներում գնահատվել են մարզում խաղողագործության զարգացման հնարավորությունները և նախապայմանները։ Виноградарство является одной из самых главных отраслей сельского хозяйства в Армавирской области РА. За последние 30 лет независимости этот сектор переживал взлеты и падения и в настоящее время имеет тенденцию развития, которую нельзя охарактеризовать как линейную и растущую. Данное исследование посвящено оценке современного состояния виноградарства в Армавирской области РА. Основной целью исследования является выявление существующих препятствий, препятствующих дальнейшему развитию отрасли. В рамках этой цели были оценены возможности и предпосылки дальнейшего развития виноградарства в Армавирской области.
Keywords: Ecology